Evaluation of the Efficiency of an Elevated Temperature Proton Exchange Membrane Water Electrolysis System. Issue 9 (20th September 2021) - Bonanno, Marco; Müller, Karsten; Bensmann, Boris; Hanke-Rauschenbach, Richard; Peach, Retha; Thiele, Simon
Abstract : In recent years, a significant interest has been growing in elevated temperature (ET) electrolytes for proton exchange membrane water electrolysis (PEMWE). In this study, the energy and exergy analysis developed for PEMWE has been extended to evaluate the performance of ET-PEMWE, with the model aiming to utilise the energy in the most efficient manner and also take into account potential heat losses. The latter is particularly important considering that heat losses become more pronounced with higher temperature differences. The model shows that the stack operates in autothermic mode over a considerable range of current density. Thus heating inputs to the stack and feed water become progressively unnecessary as polarization losses make up for these heating requirements. This also allows surplus heat to be utilised for secondary applications. The exergy efficiency for ET has been calculated to surpass that for low temperature (LT), with the maximum improvement reaching 3.8% points. Taking into account exergy favours higher temperature differences—a benefit which outweighs the fact that a greater quantity of thermal power is recovered in the LT system (due to higher polarization losses). This finding also shows the suitability of adopting exergy efficiency as the performance indicator for PEMWE systems.